Customer Data Management For Citynet Using Geolocation-Based Internet Broadband Registration Form Application - Alfiano Aldo Pamungkas; Kustiyono (P3M Politeknik Negeri Bengkalis, 2025)
This study aims to address the inefficiencies in CityNet's customer data management by developing a geolocation-based registration form application. Currently, CityNet relies on Google Forms for data collection and WhatsApp for location sharing, leading to inaccuracies, inefficiencies, and delays in the installation process. The proposed system integrates geolocation to automatically capture customer locations, reducing input errors and streamlining data processing. This research follows the waterfall development model, encompassing needs analysis, system design, implementation, and usability testing involving CityNet administrators and customers. The results indicate an 80% reduction in input errors and a 30% improvement in operational efficiency. Additionally, the system seamlessly integrates with Google Spreadsheet, Telegram, and email, ensuring real-time data synchronisation and faster response times. While the application significantly enhances CityNet's operational workflow, challenges such as user adoption and dependency on internet connectivity remain. This study provides a scalable solution for broadband providers seeking efficient customer data management with location-based automation.